Preparation of composite retentive areas for removable partial denture retainers - Pavarina, Ana Claudia [UNESP]; Machado, Ana Lucia [UNESP]; Vergani, Carlos Eduardo [UNESP]; Giampaolo, E. T. (Mosby, Inc, 2002)
A method is presented in which light-polymerized composite material is used to obtain retention for a removable partial denture when usable natural tooth undercuts are unavailable. The desired contour is waxed on a diagnostic cast with the use of a surveyor, captured in a light-polymerizing temporary restorative material, and reproduced in composite resin on the abutment teeth.